Common Mental Disorders and Equity in Health Care Use: São Paulo-Capital Health Survey - Gianini, Reinaldo José; Santos, Gustavo Venâncio dos; Salvestro, Gabriel (British Journal of Healthcare and Medical Research, 2022)
Background: Common Mental Disorders (CMDs) compromise quality of life, thus generating socioeconomic costs. Objectives: To analyze equity regarding use of the services and health expenditures among individuals with CMDs, and their relationships with sociodemographic variables. Methodology: The data are from the 2015 São Paulo health survey, with application of SRQ-20. The participants have given their consent for their data to be used in this research. Results: The sample presented a CMD prevalence of 19.7% (95% CI=18.2%-21.4%). Higher CMD prevalence values were found among users of the public health services (PR=1.49; 95% CI=1.25-1.76) and in groups with ≥ 33 dollars of health expenditures in the last month (PR=1.28; 95% CI=1.08-1.52). For individuals with CMDs, the main variables associated with “used the public health system” and “health expenditure < 33 dollars” were lower schooling levels, lower per capita family income, and age < 60 years old. There was an inverse relationship between use of the Unified Health System (Sistema Único de Saúde, SUS) and health expenditure. Conclusion: Use of the SUS by people with CMDs follows the principle of equity in that it assists groups that are underprivileged in terms of schooling and family income, but not those over 60 years old.